Job satisfaction of men and women employed in manufacturing sector and education in Serbia - Vukonjanski, Jelena; Terek, Edit; Gligorović, Bojana (The European Journal of Applied Economics, 2014)
This paper presents the results of the research on job satisfaction of men and women employed in manufacturing sector and in education sectors in Serbia. The surveys were conducted in Serbian enterprises, as well as in Serbian primary schools. In the first survey, the data were obtained by questioning N1=256 middle managers, from 131 companies in Serbia. The sample comprised 136 men and 120 women. In the second survey, the data were obtained by questioning N2=362 teachers, from 57 primary schools in Serbia. The sample included 250 women and 112 men. T-test was used for statistical analysis. Specifically, three t-tests were used for the following groups of data: job satisfaction in industrial sector and job satisfaction in education; job satisfaction of men in manufacturing sector and job satisfaction of women in manufacturing sector; job satisfaction of men in education and job satisfaction of women in education. The main conclusions are as follows: employee job satisfaction is higher in education than in industrial sector; job satisfaction in industrial sector is higher for men than for women; job satisfaction in education is slightly higher for women than for men.